Effects of CYP2D6 genetic polymorphisms on the efficacy and safety of fluvoxamine in patients with depressive disorder and comorbid alcohol use disorder - Zastrozhin MS; Grishina EA; Denisenko NP; Skryabin VY; Markov DD; Savchenko LM; Bryun EA; Sychev DA (Dove Medical Press, 2018)
Mikhail Sergeevich Zastrozhin,1,2 Elena Anatolievna Grishina,3 Nataliya Petrovna Denisenko,3 Valentin Yurievich Skryabin,2 Dmitry Dmitrievich Markov,3 Ludmila Mikhailovna Savchenko,1 Evgeny Alekseevich Bryun,1,2 Dmitry Alekseevich Sychev4 1Department of Addictology, Russian Medical Academy of Continuous Professional Education of the Ministry of Health of the Russian Federation, Moscow, Russia; 2Department of Addictology, Moscow Research and Practical Center on Addictions, Moscow, Russia; 3Research Centre, Russian Medical Academy of Continuous Professional Education of the Ministry of Health of the Russian Federation, Research Centre, Moscow, Russia; 4Department of Clinical Pharmacology and Therapy, Russian Medical Academy of Continuous Professional Education of the Ministry of Health of the Russian Federation, Moscow, Russia Background: Fluvoxamine therapy is used for treatment of patients with depressive disorder, but it is often ineffective, and some patients suffer from dose-dependent undesirable side effects such as vertigo, headache, indigestion, xerostomia, increased anxiety, etc. CYP2D6 is involved in the biotransformation of fluvoxamine. Meanwhile, the genes encoding these isoenzymes have a high level of polymorphism, which may affect the protein synthesis. Objective: The primary objective of our study was to investigate the effects of CYP2D6 genetic polymorphisms on the efficacy and safety of fluvoxamine in patients with depressive disorder and comorbid alcohol use disorder, in order to develop the algorithms of optimization of fluvoxamine therapy for reducing the risk of dose-dependent undesirable side effects and pharmacoresistance. Methods: The study involved 45 male patients (average age: 36.44±9.96 years) with depressive disorder and comorbid alcohol use disorder. A series of psychometric scales was used in the research. Genotyping of CYP2D6 (1846G>A) was performed using real-time polymerase chain reaction. Results: According to results of Mann–Whitney U-test, statistically significant differences between the efficacy and safety of fluvoxamine were obtained on 9th and 16th days of therapy in patients with GG and GA genotypes (The Hamilton Rating Scale for Depression: 10.0 [10.0; 23.0] vs 25.0 [24.0; 16.0] (P<0.001) on the 9th day and 4.0 [2.0; 5.0] vs 6.0 [6.0; 7.0] on the 16th day; The UKU Side Effect Rating Scale: 6.0 [4.0; 6.0] vs 9.0 [9.0; 10.0] (P<0.001) on the 9th day and 5.0 [1.0; 9.0] vs 19.0 [18.0; 22.0] on the 16th day). Conclusion: This study demonstrated the lower efficacy and safety of fluvoxamine in patients with depressive disorder and comorbid alcohol use disorders with GA genotype in CYP2D6 1846G>A polymorphic marker. Keywords: pharmacogenetics, SSRIs, fluvoxamine, biotransformation, personalized medicine, CYP2D6, depressive disorders, alcohol addiction